VisionaryVR: An Optical Simulation Tool for Evaluating and Optimizing Vision Correction Solutions in Virtual Reality - Benedikt W. Hosp; Martin Dechant; Yannick Sauer; Björn Severitt; Rajat Agarwala; Siegfried Wahl (Sensors, 2024)
In the rapidly advancing field of vision science, traditional research approaches struggle to accurately simulate and evaluate vision correction methods, leading to time-consuming evaluations with limited scope and flexibility. To overcome these challenges, we introduce ‘VisionaryVR’, a virtual reality (VR) simulation framework designed to enhance optical simulation fidelity and broaden experimental capabilities. VisionaryVR leverages a versatile VR environment to support dynamic vision tasks and integrates comprehensive eye-tracking functionality. Its experiment manager’s scene-loading feature fosters a scalable and flexible research platform. Preliminary validation through an empirical study has demonstrated VisionaryVR’s effectiveness in replicating a wide range of visual impairments and providing a robust platform for evaluating vision correction solutions. Key findings indicate a significant improvement in evaluating vision correction methods and user experience, underscoring VisionaryVR’s potential to transform vision science research by bridging the gap between theoretical concepts and their practical applications. This validation underscores VisionaryVR’s contribution to overcoming traditional methodological limitations and establishing a foundational framework for research innovation in vision science.